The Role of Islamic Phylantropic Institutions in Distribution of ZIS During Ramadhan to the Community in Deme 2 Village North Gorontalo, Indonesia - Harnia, Siti (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2021)
Philanthropy institutions are forums for the management of zakat, infaq, and alms to utilize zakat, infaq, and alms more maximum will be managed by the Government in this case Baznas which has a collection unit up to the village level. To have the option to increase the distribution of zakat, infaq and zakat, amil zakat organizations must gain the trust of the local area. An important component of a reliable institution is the responsibility it demonstrates. Based on this, this study intends to find out how the role of the Islamic Philanthropy Institute in the delivery of ZIS in the month of Ramadan by contextual analysis in Deme 2 Village, East Sumalata Region, North Gorontalo Regency. The research method used is field research . The researcher uses aapproach phenomenological including the latest literature from library materials and journals, data is collected through observation, documents and interviews, then the data is analyzed sequentially and interactionist which consists of three stages, namely: ) Data reduction, 2) Data presentation, 3) Conclusion drawing or verification. The results of the study reveal that the existence of this philanthropic institution is very beneficial for individuals in Deme 2 Village, East Sumalata Region, North Gorontalo Regency. Through various assistance provided by the institution, it is possible to build a strengthening of the nearest network. If the beneficiary have difficulty in meeting their daily needs, after receiving the assistance provided by the agency they have the option of meeting their daily needs during the month of Ramadan and especially during the holidays. Eid Al-Fitr. So that with the assistance provided by the Institute, it can empower the surrounding environment.